2012
DOI: 10.1136/sextrans-2012-050490
|View full text |Cite
|
Sign up to set email alerts
|

Repeat genitalChlamydia trachomatistesting rates in young adults in England, 2010

Abstract: We observed moderate levels of repeat testing within a year. Considering the frequency of partner change among young people, more could be done to encourage re-testing upon change of sexual partner. Increasing re-testing following a positive test could probably identify unresolved or repeat infections that may otherwise go untreated. Work to establish the optimum approach to repeat testing in England is now warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
19
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
3
19
2
Order By: Relevance
“…Having STI-related symptoms and being notified were clear factors associated with reinfection in the current study. This finding concurs with other studies 3 5 10 17 18…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Having STI-related symptoms and being notified were clear factors associated with reinfection in the current study. This finding concurs with other studies 3 5 10 17 18…”
Section: Discussionsupporting
confidence: 94%
“…Despite the limitations, this study and other studies conclude that young people with chlamydia are at risk for reinfection and that it is important to retest them and preferably remind them of the retest 3 5 10 17 18. This study has been performed within a standard care environment, complying with the criteria for access to free STI care at STI clinics in the Netherlands, simplifying potential future implementation.…”
Section: Discussionmentioning
confidence: 99%
“…First, we know from prospective8–11 and passive12 13 follow-up studies that individuals who test positive for chlamydia are at considerably higher risk of subsequent chlamydia infection than those who test negative. Retesting could therefore lead to considerably greater numbers of infections being diagnosed and treated.…”
mentioning
confidence: 99%
“…Woodhall et al 7 examined repeat testing within the English chlamydia screening programme and found that the risk of infection at retest was approximately twice as high in persons who initially tested positive compared to those negative. Turner et al similarly found a doubling of risk in a study of retesting in Cornwall (Turner et al 8).…”
mentioning
confidence: 99%
“…Turner et al similarly found a doubling of risk in a study of retesting in Cornwall (Turner et al 8). Despite the high risk of reinfection observed, the overall rate of repeat testing was relatively low, with 75% of individuals in Cornwall only testing once between 2003–20098 and 85% only tested once in England within 2010 only 7. Heijne et al 9 address the question of when retesting should occur, using data from the USA and a mathematical model.…”
mentioning
confidence: 99%